PERFORMAN PERTUMBUHAN AWAL AYAM BURAS PADA FASE STARTER YANG DIBERI RANSUM KOMERSIL AYAM BROILER - Arnold Ch. Tabun; Bernadus Ndoen (Politeknik Pertanian Negeri Kupang, 2009)
Buras (local) chicken at starter phase were treated with broiler commercial feeds for their performances. TheÂ research was conducted at Laboratory of Animal Productin and Reproduction of Kupang State Agricultural Polytechnic. The aims of this research were to measure the earlyÂ preformance of buras chicken (stain KS 808) and to know the kind of coercial feed which give more effective effect on daily gain. Experimental design whichÂ used is complitely randomize design which consist of 3 tretaments and 5 replication. The commercial feed treatments are: PI ( BR I), P2 ( CP 11) and P3 ( 511).The giving of starter feed BR1, CP 11 dan CP 511 to buras chiken showed that average weekly consuption is 320,065gr/head/week, feed convertion is 0,456 and average gain is 203 gr/head/week. All kinds of commercial feed give the same effect on feed consumption, feed convertion and daily gain, so three kinds of commercial feed can be used in buras chicken production.Keyword : Native chicken, starter phase, feed consumption, feed convertion, daily gain